Solar illumination control of ionospheric outflow above polar cap arcs. Issue 5 (12th March 2015) - Maes, L.; Maggiolo, R.; De Keyser, J.; Dandouras, I.; Fear, R. C.; Fontaine, D.; Haaland, S.
Abstract: We measure the flux density, composition, and energy of outflowing ions above the polar cap, accelerated by quasi‐static electric fields parallel to the magnetic field and associated with polar cap arcs, using Cluster. Mapping the spacecraft position to its ionospheric foot point, we analyze the dependence of these parameters on the solar zenith angle (SZA). We find a clear transition at SZA between ∼94° and ∼107°, with the O + flux higher above the sunlit ionosphere. This dependence on the illumination of the local ionosphere indicates that significant O + upflow occurs locally above the polar ionosphere. The same is found for H +, but to a lesser extent. This effect can result in a seasonal variation of the total ion upflow from the polar ionosphere. Furthermore, we show that low‐magnitude field‐aligned potential drops are preferentially observed above the sunlit ionosphere, suggesting a feedback effect of ionospheric conductivity. Key Points: Strong effect of sunlit/dark ionosphere in the ion outflow above polar cap arcs Outflow from local ionosphere so possibly also O + ions in the polar wind Low‐magnitude field‐aligned potential drops only observed above sunlit polar cap